Cooperative Research Centers and Technical Innovation Government Policies, Industry Strategies, and Organizational Dynamics - Boardman, Craig; Gray, Denis O.; Rivers, Drew.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
At a time when scientific and technical innovation now requires a multitude of heterogeneous inputs and expertise from the public and private sectors alike, cooperative research centers (CRCs) have emerged as the predominant vehicle for cross-sector collaboration. In the U.S. alone, there are thousands of CRCs on university campuses, and agencies like the National Science Foundation, National Institutes of Health, Department of Defense, and more recently the Department of Energy fund CRCs to address some of the nation$1 (Bs most formidable challenges with science and technology, including cancer and other diseases, terrorism surveillance and the detection of weapons of mass destruction, and new energy technologies and smart enegry grid development. Industry oftentimes participates in CRCs for access to knowledge, capacity development, and to mitigate risk. This volume includes research investigating CRCs from North America, Europe, Australia, and Asia to explore the dynamics of CRCs, including but not limited to resource allocation, structure, level of sponsorship, organization and membership, management and operations, objectives and goals, and in doing so identifies both differences and similarities across institutional and national contexts. The volume sheds light on the role of CRCs in promoting innovation, S&T policy, and economic development, and on the practical aspects of successful CRC management. Moreover, the works included in the volume consider the implications for the various stakeholder groups (firms, universities, researchers, students, policymakers) invested in CRCs.s
Keywords: Economics; Endogenous growth (Economics).; Economic policy; Economics/Management Science; R & D/Technology Policy; Economic Growth; Economic Policy